Research on Failure Characteristics and Zoning Control Technology of Thick-Soft Surrounding Rock for Deep Gob-Side Entry Retaining - Jingke Wu; Wenbin Zhou; Hong Tao; Haowen Bai; Wei Yin; Wenhu Gu; Peng Zhang; Zejun Liu; Jiao Zhang (Shock and Vibration)
Controlling the large deformation caused by bed separation failure of thick and soft surrounding rock in gob-side entry retaining is difficult. The deformation and failure modes of thick and soft surrounding rock are summarized and classified based on field research, theoretical analysis, laboratory tests, and actual measurements. Systematic research is conducted on the lithologic characteristics, failure characteristics, and control methods of the surrounding rock. The research findings are as follows: (1) The low strength, softening, and water swelling of thick mudstone, as well as its cataclasis, dilatancy, and long-term creep under strong mining and high stress are the objective reasons for large deformation of the surrounding rock. (2) Due to the weak stability of the surrounding rock-support structure and low collaborative roof side bearing capacity, no complete supporting structure is formed with the supporting system, causing the support body in each area to be crushed one by one, which is the subjective reason for the deformation and failure of the surrounding rock. (3) The deformation and failure characteristics of thick and soft surrounding rock in gob-side entry retaining are primarily divided into eight types: roof bending and sinking type, roof cutting along filling body, rib spalling type, roof fall type, filling body rotation type, filling body crushing type, roof step type, and roof cutting along the coal side. The initial points and key points for a chain reaction of each failure type are determined. (4) The surrounding rock is divided into 10 support zones at four levels, and control technology for “zonal support and overall reinforcement” is put forward. The mechanical effect of the support body in each zone and its role in maintaining the stability of surrounding rock are analyzed. This technology can ensure the integrity of the surrounding rock structure and improve the roof side collaborative bearing capacity.